Establishment of a Multiplex RT-PCR Method for the Detection of Five Known Genotypes of Porcine Astroviruses - Liu, Xin; Zhang, Wenchao; Wang, Dongjing; Zhu, Xinyue; Chen, Ying; Ouyang, Kang; Wei, Zuzhang; Liu, Huan; Huang, Weijian (Frontiers in Veterinary Science, 2021)
Porcine astroviruses (PAstVs) are prevalent in pigs worldwide, and five genotypes have been reported to circulate in China. However, little is known about the coinfection status of PAstVs. For differential and simultaneous diagnoses of these five genotypes of PAstVs, a multiplex RT-PCR method was established on the basis of the ORF2 gene of type 1 PAstV, and the ORF1ab genes of type two to five PAstVs. This quintuple PCR system was developed through optimization of multiplex PCR and detection sensitivity and specificity. The results showed that this multiplex RT-PCR method could specifically detect all the five PAstV genotypes without cross-reaction to any other major viruses circulating in Chinese pig farms. The detection limit of this method was as low as 10 pg of standard plasmids of each PAstV genotype. In addition, a total of 275 fecal samples collected from different districts of Guangxi, China, between April 2019 and November 2020, were tested by this newly established multiplex RT-PCR. Moreover, the sensitivity and specificity of monoplex and multiplex RT-PCR methods were compared by detecting the same set of clinical positive samples. The results revealed that PAstV1 (31/275), PAstV2 (49/275), PAstV3 (36/275), PAstV4 (41/275), and PAstV5 (22/275) were all detected, and dual (PAstV1+PAstV2, PAstV1+PAstV3, PAstV2+PAstV3, PAstV2+PAstV4, PAstV3+PAstV4, and PAstV4+PAstV5) or triple genotypes (PAstV1+PAstV2+PAstV3 and PAstV2+PAstV3+PAstV4) of coinfections were also unveiled in this study. The detection result of multiplex PCR was consistent with that of monoplex PCR. Compared with monoplex PCR, this multiplex PCR method showed obvious advantages such as time and cost efficiency and high sensitivity and specificity. This multiplex RT-PCR method offered a valuable tool for the rapid and accurate detection of PAstV genotypes circulating in pig herds and will facilitate the surveillance of PAstV coinfection status.